Utilization of chicken eggshell and chitosan as coagulants for microplastic removal from aquatic system - Aaron Nathanael Liemin; Monica Kezia Sembiring; H Hadiyanto (Journal of Bioresources and Environmental Sciences, 2023)
Smaller size plastics known as microplastics are harmful for marine biota as well as humans. One of the common methods for the removal of microplastics from water is coagulation. Chicken eggshells and chitosan are two natural ingredients which contain useful content for the coagulation process. Therefore, this paper describes the effect of concentration of eggshells and chitosan as coagulants in the separation of microplastic from water using RSM (Response Surface Methodology). The effect of tannic acid concentration as coagulation aid was also analyzed in this paper. The coagulants were varied with concentration of 1.5-8.5 g/100 mL and tannic acid concentration was 3-17 mg/100 mL. The result of this study showed coagulation with the highest efficiency occurred when 8.5 g/100 mL of chicken eggshell coagulant (89.14%) and 10 g/100 mL chitosan coagulant (75.67%) was added. Optimum operation occurred after the addition of coagulant aid in the amount of 7 mg/100 mL with chicken eggshell and 15 mg/100 mL with chitosan.